Tension Control UCL Reconstruction With Internal Brace Augmentation - Sercan Yalcin MD; Jacob Maier MD; Mark Schickendantz MD; Salvatore Frangiamore MD (SAGE Publishing, 2022)
Background: Ulnar collateral ligament (UCL) rupture is a common injury, particularly in throwing athletes. It occurs either in the acute setting or due to repetitive microtrauma. UCL reconstruction has been a successful treatment with proper patient selection. A number of different surgical techniques have been described in the literature. We developed a novel surgical technique using internal brace augmentation to address the 2 most common causes of failure: suture failure and bone tunnel fracture. Indications: To provide information about this novel UCL reconstruction technique. Technique Description: The palmaris longus graft is harvested and prepared to be used as the autograft. A 5-cm curved incision is made over the medial epicondyle of the humerus. The UCL reconstruction is then performed using the double suspensory reconstruction technique followed by an internal brace augmentation. Results: Excellent clinical outcomes and high return to sports rates have been reported after UCL reconstruction. In this novel technique, the addition of the internal brace provides secondary interference fixation of the graft on the humeral side along with the additional support the brace itself provides. Discussion/Conclusion: Using internal brace augmentation increases the stability of the UCL reconstruction while preventing suture failure and bone tunnel fracture.